2018
DOI: 10.1016/j.devcel.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Yorkie Functions at the Cell Cortex to Promote Myosin Activation in a Non-transcriptional Manner

Abstract: The Hippo signaling pathway is an evolutionarily conserved mechanism that controls organ size in animals. Yorkie is well known as a transcriptional co-activator that functions downstream of the Hippo pathway to positively regulate transcription of genes that promote tissue growth. Recent studies have shown that increased myosin activity activates both Yorkie and its vertebrate orthologue YAP, resulting in increased nuclear localization and tissue growth. Here we show that Yorkie also can accumulate at the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 64 publications
(74 reference statements)
6
34
0
Order By: Relevance
“…12A). These findings together with previous observations in wing imaginal disc (Xu et al, 2018) point to a transcription-independent role of Yki in the apical cell cortex to regulate the apical cytoskeleton. Second, residual Yki molecules, which do not bind Tsr, are free to translocate to the nucleus and transcribe Alas to regulate crosslinking of cuticular proteins, and genes involved in in tissue size regulation, such as diap1 (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…12A). These findings together with previous observations in wing imaginal disc (Xu et al, 2018) point to a transcription-independent role of Yki in the apical cell cortex to regulate the apical cytoskeleton. Second, residual Yki molecules, which do not bind Tsr, are free to translocate to the nucleus and transcribe Alas to regulate crosslinking of cuticular proteins, and genes involved in in tissue size regulation, such as diap1 (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Upon cortical tension increase and Yorkie activation, this transcriptional co-activator promotes cell growth, proliferation, and tension decrease (Pan et al, 2016). Lastly, recent work reported that cortical Yki can also promote Myo activation in a transcriptional-independent manner (Xu et al, 2018). New Role for Wnt/b-Cat Signaling in Epithelial Tissue Mechanosensing b-cat, a core component of the cadherin adhesive complex, is able to respond to Wnt ligands and act as a transcriptional coactivator.…”
Section: Sensing Mechanical Forces Via Hippo or Yap Signalingmentioning
confidence: 99%
“…Feedback loops through Yki, such as a short one through dmyc (Neto‐Silva, de Beco, & Johnston, ), can serve to limit Yki signaling, while other feedback targets include crumbs , ds , expanded , merlin , wts , kibra , and four‐jointed ( fj ) (Cho et al, ; Enderle & McNeill, ; Fulford, Tapon, & Ribeiro, ; Ikmi et al, ; Irvine, ; Nolo, Morrison, Tao, Zhang, & Halder, ; Oh & Irvine, ; Wang, Zhang, & Blair, ; Wartlick, Mumcu, Jülicher, & Gonzalez‐Gaitan, ; Zecca & Struhl, ). In addition, Yki modulates morphogen signaling by transcriptional control of the glypicans dally and dlp —which encode co‐receptors or sequestering proteins for Dpp and Wg (Baena‐Lopez, Rodríguez, & Baonza, ; Fujise et al, ; Kreuger et al, )—and Yki also activates myosin at the membrane (Xu et al, ). Following establishment of the DV boundary there are four compartments in the wing pouch, each of which evolves independently to a certain degree.…”
Section: Introductionmentioning
confidence: 99%